Infantile myofibromatosis - Margarita Larralde; Bruno Ferrari; Juan Pablo Martinez; María Angélica Fernández Barbieri; José Higinio Méndez; José Casas (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Infantile myofibromatosis is a mesenchymal disorder characterized by the fibrous proliferation of the skin, bone, muscle and viscera. It is the most common fibrous tumor in childhood. We present a newborn with skin and bone disease without visceral involvement, who showed good response to vinblastine and methotrexate. Clinical features, etiology, diagnosis, and treatment are reviewed.